Studies on the disinfection efficiency of hoa sen medical instrument sterilizing equipment at the general, obstetrics and paediatrics hospitals in TraVinh Province - Long, Pham Hoang; Chau, Nguyen Hoai; Thanh, Nguyen Chi; Buu, Ngo Quoc (Academia Journal of Biology, 2019)
This research aims to study on the disinfection efficiency of Hoa Sen medical instrument sterilizing equipment based on the application of ECA technology at General Hospital and Obstetrics and Paediatrics Hospitals in Tra Vinh. Disinfection using ECA technology is a method that does not require the introduction of special oxidizing agents except of water and salt. ECA solution - Anolyte solution has very strong oxidants, which oxidize components such as protein, lipid, etc. (usually of the bacterial cell membrane) that make the cell membrane decomposed, reducing 77−93% of the respiratory ability of bacterial cells, weakening them and eventually being destroyed. Hoa Sen medical instrument sterilizing equipment has a similar construction form as a regular double washing table with two wash basins, wherein one sink with a faucet which produces purified water, while other one has a faucet that gives anolyte solution for sterilization. Both faucets are based on a touch support. At the bottom of the sink an anolyte solution production system was installed. Valorization of the disinfection ability of the Hoa Sen medical instrument sterilizing equipment was based on the determination of the number of microorganisms on the surface of the instrument before and after being soaked with an antiseptic washing table. Microbiological criteria are the number of aerobic bacteria, E. Coli and Coliforms. Analytical samples were quantified by culture method on agar plates. Analysis of total aerobic bacteria, E. Coli and Coliforms bacteria according to Vietnam Standard TCVN 4884:2015, TCVN 6846:2007 and TCVN 6848:2007, respectively. The results showed that bacterial removal efficiency was elevated with a novel Hoa Sen sterilizing equipment anolyte. In laboratory scale, E. Coli and Coliforms bacteria with a density of 105 CFU/mL were completely removed in 30 sec contact with an anolyte solution of 300 mg/L active chlorine concentration. In hospital scale, the removal efficiency of total aerobic bacteria on the surface of medical instruments after surgery was 99% for one minute disinfection time. For E. Coli and Coliforms bacteria, the results of the analysis were not detected in both cases before and after sterilization.